Penggunaan Metode Waterfall untuk Rancangan Bangun Aplikasi Penyewaan Lapangan Olahraga - Rachmat Hidayat; Arief Satriansyah; M. Sinta Nurhayati (Puslitbang Sinergis Asa Professional, 2022)
Buaran sports field, is a multifunctional sports venue for volleyball, futsal, badminton and basketball fields, currently the field is always used every day there is never a vacancy. The sports field rental business is one of the business fields that is quite developed, knowing this the management must have new breakthroughs so that customers do not move to other places. Managers are faced with the challenge of how they can improve services and provide the information needed to customers. The purpose of this research is to find out how to improve services to users related to field rental information, namely by designing a web-based field rental information system with the Waterfall method where data collection will be carried out. observation and interviews as analytical tools. From the results of the study it was concluded that an integrated information system with customers can be accessed 24 hours and is also expected to assist officers in managing financial transactions and can reduce errors in the data collection process, and there will be no more misinformation and reporting will be easier because the data is already stored. in database